1974
DOI: 10.1104/pp.53.5.728
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Acids in Wheat Coleoptile Cell Walls

Abstract: The phenolic constituent of nonvascular cell walls of wheat (Triticum aestivum L.) coleoptiles, which yields vanillin upon nitrobenzene oxidation, is not lignin as I previously claimed. It seems to be mainly ferulic acid bonded to carbohydrate, probably by an ester linkage. The acid is associated with a fraction of the wall rich in arabinose and xylose, although it is not known whether it is esterified directly with these pentose residues. The phenolic-carbohydrate complex is released by cellulase, but not by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Ferulic acid is present in many cutins and suberins (Holloway 1981(Holloway , 1984 but it is not a characteristic constituent of plant cutins. Ferulic acid has been found in leaf (Hartley 1973;Hartley and Jones 1977), coleoptile (Whitmore 1974), and scutellure (Smart and O'Brian 1979) cell walls, and in lignified tissues (Schwarz et al 1989) of Gramineae. It is thus likely that substantial portions of the amounts of ferulic acids found in the depolymerisates did not originate from cutin or suberin but rather from cell walls and lignin.…”
Section: Resultsmentioning
confidence: 97%
“…Ferulic acid is present in many cutins and suberins (Holloway 1981(Holloway , 1984 but it is not a characteristic constituent of plant cutins. Ferulic acid has been found in leaf (Hartley 1973;Hartley and Jones 1977), coleoptile (Whitmore 1974), and scutellure (Smart and O'Brian 1979) cell walls, and in lignified tissues (Schwarz et al 1989) of Gramineae. It is thus likely that substantial portions of the amounts of ferulic acids found in the depolymerisates did not originate from cutin or suberin but rather from cell walls and lignin.…”
Section: Resultsmentioning
confidence: 97%
“…Initially, it was thought that this ferulic acid was ester-bonded only to lignin (Higuchi et al 1967;Whitmore 1974). However, further studies showed that it is also ester-bonded to wall polysaccharides (Hartley 1973;Hartley and Jones 1976) and that such feruloylation occurs also in some dicots (Fry 1979;Hartley and Harris 1981) and non-Poaceae monocots (Harris and Hartley 1980).…”
Section: Introductionmentioning
confidence: 97%
“…Hydroxyproline-rich glycoproteins are abundant in walls of dicots (10,22), but are minor constituents of the walls of cereals and other grasses. On the other hand, phenolic substances have been observed by fluorescence microscopy throughout the primary walls of grass tissues (17,19); ferulic acid has been identified unequivocally as a major phenolic compound (12,13,19,21,27,29,31), and its esterification to hemicellulosic arabinoxylans has been documented (21,27). Moreover, Markwalder and Neukom (23) have also identified diferulic acid in wheat flour and implicated this ferulate biphenyl dimer in crosslinking the water-soluble pentosans into an insoluble matrix.…”
mentioning
confidence: 99%
“…The proportion and composition of these fractions varied markedly during coleoptile development (7). In related studies, treatment of walls of maize coleoptiles with acidic sodium chlorite to oxidize phenolic substances rendered much ofthe hemicelluilosic material soluble in as little as 0.02 N KOH (6 (29). Much more concentrated alkali is required to solubilize most of the hemicellulosic polysaccharide before sodium chlorite treatment, so many of these polymers may be cross-linked by phenolic linkages other than esterified diferulic acid.…”
mentioning
confidence: 99%